Black Soldier – Patron Saint: St Maurice and the Livonian Merchants - Anu Mänd (ICO Iconographisk Post, 2014)
This article discusses the cult and visual representation of St Maurice in late medieval Livonia (i.e. present day Estonia and Latvia), set in the broader context of the Baltic Sea region. The main, but not the only, promoters of his cult were the confraternities of the Black Heads – associations of journeyman merchants, existing in the three largest Livonian Hanse towns from the early fifteenth century onwards. The aim of the article is to offer explanations about why these associations chose warrior saints as their identity markers and why St Maurice figured so prominently among them.